Building School Capacity to Support Students with Complex Needs Through the Wellness, Resiliency, and Partnerships (WRaP) Project - Tremblay, Melissa Krystal; Mastrangelo, Tracy; Pei, Jacqueline (Alberta Journal of Educational Research, 2021)
Schools across the province of Alberta are increasingly diverse in terms of student backgrounds, circumstances, and needs (Alberta Education, 2017). In order to respond to the needs of a diverse student population, many schools are providing supports targeted to children and youth identified as being at risk for poor outcomes. The Wellness, Resiliency, and Partnerships (WRaP) project, initiated in 2009, was born out of recognition for the need to provide individualized, strength-based supports to students with Fetal Alcohol Spectrum Disorder (FASD). For eight years, WRaP success coaches aimed to provide innovative, collaborative, strength-based services and supports to promote the success of students with FASD in Alberta schools. The project initially targeted junior and senior high school students with FASD. Over the project’s most recent two years, the project expanded to serve elementary schools, as well as students with complex needs in addition to those that arise due to FASD. The aims of the project were to maximize school engagement, increase academic success, and enhance social, emotional, and physical well-being. In addition, coaches worked to enhance school and family capacity to support students with complex needs, and to build partnerships for youth to access supports at home, at school, and in their communities. Overall, the WRaP project demonstrated significant growth and positive outcomes in terms of building school capacity to support students with complex needs including FASD. We will draw on data from four years of annual interviews and focus groups conducted with WRaP success coaches and school personnel to describe the key processes, successes, and challenges involved in building school capacity through the WRaP project in Alberta schools. Key words: Fetal alcohol spectrum disorder; community-based participatory research; school capacity building; mentorship; students with complex needs Partout en Alberta, les écoles servent une population d’élèves dont les antécédents, les circonstances et les besoins sont de plus en plus diversifiés (Alberta Education, 2017). Afin de répondre aux besoins d’une population d’élèves diversifiée, plusieurs écoles fournissent des appuis visant les enfants et les jeunes identifiés comme étant à risque de connaitre de mauvais résultats scolaires. Le projet WRaP (Wellness, Resiliency, and Partnerships; c.-à-d., bien-être, résilience et partenariats), initié en 2009, est né de la reconnaissance du besoin d’offrir des appuis individualisés et axés sur les besoins des élèves atteints du syndrome de l'alcoolisation fœtale (SAF). Pendant huit ans, les entraineurs motivateurs de WRaP ont œuvré pour fournir des services et des appuis innovateurs et collaboratifs qui visaient les besoins des élèves albertains atteints du SAF. Initialement, le projet visait les élèves albertains de la 7e à la 12e année atteints du SAF, mais au cours des deux dernières années, le projet a été étendu pour inclure les écoles élémentaires ainsi que les élèves ayant des besoins complexes au-delà de ceux qui découlent du SAF. Les objectifs du projet étaient de maximiser la participation à l’école, augmenter la réussite académique et rehausser le bien-être social, émotionnel et physique. Les entraineurs ont également travaillé au renforcement de la capacité des écoles et des familles pour soutenir les élèves ayant des besoins complexes et à la création de partenariats permettant aux jeunes d’accéder aux appuis à la maison, à l’école et dans leurs communautés. Globalement, le projet WRaP a démontré des progrès significatifs et des résultats positifs quant au renforcement de la capacité des écoles pour soutenir les élèves ayant des besoins complexes, y compris le SAF. Puisant dans des données provenant de quatre séries d’entrevues annuelles et de groupes de discussion formés d’entraineurs motivateurs et de personnel scolaire, nous décrivons les processus clés, les réussites et les défis liés au renforcement de la capacité scolaire par le biais du projet WRaP dans les écoles en Alberta. Mots clés : syndrome de l'alcoolisation fœtale; recherche participative basée sur la communauté; renforcement de la capacité scolaire; mentorat; élèves ayant des besoins complexes